Aspectos subjetivos determinantes da gravidez reincidente naadolescência: uma abordagem a partir da psicanálise - Teresa Cristina Paulino de Mendonca (2012)
This study is the result of a research realized through semi-structured interviews with adolescent mothers that gave birth to one or more children up until the age of 21 years old. This study aimed to investigate the determining subjective aspects of the recurrent adolescent pregnancy, based on the psychoanalysis theory. It proposes the reflection about the place, within the subjectivity, motherhood can occupy to those adolescents, and, if being a mother has answered them the enigma of the feminine. A brief bibliographical scientific revision was done concerning the repetition of adolescent pregnancy, and the specificities of this phase of development of those subjects was approached, verifying that the awakening of the sexuality happens at the adolescence, which is unbearable while real, impossible to symbolize, that urges on and leaves the young speechless. The adolescence pregnancy was discussed as an answer of the pulsional exceeding, as an attempting of recovering the constitutive lack of these subjects; as a contemporary symptom, time of the fall of the ideals. The development and the constitution of the femininity (the woman is not-all inscribed in the phallic order), since the Freudian pre Oedipus up until the Lacanian conception of the no representation of the feminine within the unconscious (the woman doesn't exist) was discussed as the basis to establish the real in the relationship of the woman, as a mother, with her child. What is repeated as a lack for the adolescent is the faulty meeting with the Other and she repeats the pregnancy, as an attempting to fulfill this lack, placing the child in the place of the phallus. The repetition of adolescent pregnancy was discussed as a symptom which arouses to them as a possible answer to the impossible real to be circumscribed, which is the absence of sexual intercourse. A hypothesis of the repetition of the adolescent pregnancy being an acting-out was formulated, a path to provide the answers to the difficulties of the subject facing the castration. In the presence of the repetition of adolescence pregnancy, which is a fact that reveals an insistent attempting of the desire, conscious or not, of fulfill the original lack, we explicitly face ourselves with the question of the feminine desire, which is set to the girl.